Booklet Sebagai Media Peningkatan Pengetahuan Tentang Pendidikan Seks Anak Usia Dini Pada Orang Tua - Anaa Murti Citra Putri Azzahra; Iin Ervina; Erna Ipak Rahmawati (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2020)
Sexual violence in children has the impact of physical, mental, social and behavioral trauma in the short and long term. Therefore, prevention needs to be done, one of them is by providing sex education early on through parents. So parents need to be equipped with the knowledge of early childhood sex education.The purpose of this study was to determine the effectiveness of the booklet media for early childhood sex education on the knowledge and skills of parents in providing sex education for early childhood.The method used is a quasi-experimental research model with a research design using pretest-posttest control group design. The sample used was 40 people with the criteria of parents with children aged 1-6 years. The study was conducted at Al-Fattah Kindergarten.The results of this study indicate that the booklet is able to increase the knowledge of early childhood sex education in parents with a significance value (2-tailed) 0.038 0.05 based on the pretest and posttest paired sample test. The average pretest score was 18.60 and increased by 1.00 after being given an early childhood sex education booklet with an average score of 19.60. The highest increase occurred in the aspects of children's birth, booklet can cognitively facilitate parents in understanding sex education material, affectively able to help the readiness and willingness of parents to act, and psychomotorally can help parents educate their children.